Effect of acidity and mesoporosity in H-USY on conversion of wheat straw to ethyl levulinate (Biofuel additive) - Heda, Jidnyasa; Niphadkar, Prashant; Nandanwar, Sachin; Bokade, Vijay (Journal of the Indian Chemical Society, 2023)
Cold flow properties of biodiesel can be improved by addition of additives especially ethyl levulinate (EL up to 20%). There are very limited information on synthesis of EL from actual raw biomass like wheat straw over heterogeneous catalyst. The present article elaborated on optimization of Acidity to Mesoporosity ratio in H-USY, which is crucial for its application in conversion of raw wheat straw to selective formation of EL in one-step. The acidity and mesoporosity is monitor by systematic post treatment of desilication and dealumination. Optimum acidity/mesoporosity ratio of 3.6 in HUSY resulted in to maximum EL yield of 24.5%, which is probably the highest so far.
Keywords: Acidity; Biofuel additive; Dealumination; Desilication; ethyl levulinate; H-USY; Mesoporosity; Wheat straw